Smartphone-integrated immunosensing based on the wavelength filtering from chromogenic enzymatic reaction - Jeong, Kwan Young; Kim, Saemi; Lee, Kyung Won; Kim, Ka Ram; Chun, Hyeong Jin; Yoon, Hyun C. (23rd International Conference on Miniaturized Systems for Chemistry and Life Sciences, MicroTAS 2019, 2019)
We developed a smartphone-based optical biosensing platform which could be used as a point-of-care testing device. The developed platform is based on the principles of specific wavelength filtering effects of chromogenic enzymatic reactions, enabling intuitive handling of signals on smartphones without complex external optical instruments. Using this platform, quantitative analysis of uCTX-II was successfully performed from in concentration ranging from 0 to 10 ng/ml. Based on these results, we expect the developed optical biosensing platform had the potential that can be used in the resource-limited condition.
Keywords: Enzymatic reaction; Immunosensing; Optical bio-sensing; Point-of-care testing; Wavelength filtering; Optical Biosensing; Point-Of-Care Testing; Smartphone-based uCTX-II Biosensor; Wavelength Filtering Effect